Configuration Selection Based On Lifecycle Cost Of Subsea Production System: Case Of Indonesia Deepwater Field - Christoffel. F.B Sa'u; Daniel M Rosyid (International Journal of Marine Engineering Innovation and Research, 2018)
Subsea tie back systems are important parts of oil and gas production project. The decision to select a subsea tie-back configuration with the objective goal of lowest lifecycle cost can be configured in multiple ways based on the field specifications and operator’s approach to operation. This paper presents an Analytic Hierarchy Process (AHP) method to determine economical levels of subsea tie-back wells configuration, based on lifecycle cost of subsea deepwater production systems with respect to wells number alternative. Field reservoir located in deepwater of eastern Indonesian with the depth of 1400 meters and field life 40 years is studied. From this study, it is identified that the most economical configuration in subsea production systems: satellite tie-back configuration to develop small field with 6 numbers of wells; for 12 numbers of wells, template subsea tie-back configuration is the best.